The Eksistensi Karya Seni Rupa Islam dalam Medan Seni Rupa Indonesia: Studi Kasus Pameran Fragments of Modern Indonesian Art History di OHD Museum Magelang - Khairi, Miftahul (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2024)
This research explains the development of Islamic art in the modern and contemporary Indonesian art scene through Rispul and Tita Rubi's works collected by OHD Museum. The fundamental question is how OHD's taste in choosing its collection? How is the curation process in the exhibition Fragment of Modern Indonesian Art History? And why Rispul and Titarubi's works were chosen for the exhibition? This question is explained through the sociology of art theory from Becker and Bourdieu and uses a qualitative method with a case study approach. The results of the study show that OHD as a pure collector by providing distinction to the works he will collect, thereby gaining legitimacy in the Indonesian and Asian art scene. His legitimacy is able to influence the world of art collecting in Indonesia and Asia. The works of Tita Rubi and Rispul were collected and selected for the exhibition because they fit the criteria of being part of the development of contemporary art and continuing the Islamic art series.